Investigating The Exhaustion of Police officers, Selected Regions Within Namibia - R., Pieters W.; C., Hasheela (Journal of Economics and Behavioral Studies, 2018)
Recent studies showed that suicide among police officers are prevalent in certain countries . Burnout and subjective health complaints are considered as risks that are consistent with high levels of suicide ideation. Police officers are exposed to life-threatening traumatic experiences, such as physical assault or witnessing disturbing images of death. The aim of this study was to investigate the relationship between job demands- resources, authentic leadership, work engagement and burnout within the Namibian Police Force. A cross - sectional survey design was used collecting data about police officers in the Erongo, Oshana and Khomas regions (n=369). Data was analysed using SPPS (version, 24) and Pearson product correlations. Results indicated that when police officers experience high a workload and leaders who do not engage in the moral and ethical behaviour, they will experience higher levels of exhaustion. Factors like organisational support and resources also seemed to impact on work engagement. To reduce exhaustion and increase engagement, it is vital that the police force assesses person-job fit, implement stress management and wellness programmes to help employees cope better with work demands. Moral and ethical behaviour can be enhanced through leadership training/development. Improving on colleague relations (team building) and through mentorship programmes employees would have access to social support at work, buffering a high workload.